EXAMINATION OF THE EIGENVALUES LORENZ CHAOTIC SYSTEM - Kose, Ercan; Akcayoglu, Azize (European Scientific Journal, ESJ, 2014)
In this paper, Classical Lorenz Equations are simulated using MATLAB/Simulink, by getting the graphical outputs performances of the equations are studied. The butterfly effect was seen in the expected output graphs. Classical Lorenz Equations were linearization and then Jacobian matrix was obtained by MATLAB software in embedded system and eigenvalues calculated. The numereous eigenvalues poles were seen an the rigth axis side of the complex plane. These poles are causes the unstable behaviors.